2014
DOI: 10.1179/2047773214y.0000000134
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of acquiringStrongyloides stercoralisinfection among patients attending a tertiary hospital in Thailand

Abstract: Objectives: We aimed to determine the prevalence and risk factors for Strongyloides stercoralis infection in adult patients attending Siriraj Hospital, a tertiary hospital in Thailand. Methods: A case-control study was carried out between July 2008 and April 2010. Case and control were identified from 6022 patients for whom results of faecal examination were available. A case was a patient who had S. stercoralis larva detected from faecal examination. Control was randomly selected from patients without S. ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
3
20
0
1
Order By: Relevance
“…Hyperinfection occurs mostly in patients with an impaired cell mediated immune system (Grove, ; Huis, Sun, Hung, & Colebunders, ; Keiser & Nutman, ). Human immunodeficiency virus (HIV) infection, Human T‐cell leucemia virus type 1 (HTLV‐1) infection, alcoholism, low socioeconomic status, white race, male gender, corticosteroid therapy, hematologic malignancy and malnutrition have been reported as risk factors for strongyloidiasis (Davidson, Fletcher, & Chapman, ; Jongwutiwes, Waywa, Silpasakorn, Wanachiwanawin, & Suputtamongkol, ; Keiser & Nutman, ; SchĂ€r et al, ; Walzer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperinfection occurs mostly in patients with an impaired cell mediated immune system (Grove, ; Huis, Sun, Hung, & Colebunders, ; Keiser & Nutman, ). Human immunodeficiency virus (HIV) infection, Human T‐cell leucemia virus type 1 (HTLV‐1) infection, alcoholism, low socioeconomic status, white race, male gender, corticosteroid therapy, hematologic malignancy and malnutrition have been reported as risk factors for strongyloidiasis (Davidson, Fletcher, & Chapman, ; Jongwutiwes, Waywa, Silpasakorn, Wanachiwanawin, & Suputtamongkol, ; Keiser & Nutman, ; SchĂ€r et al, ; Walzer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Jongwutiwes et al reported a case-control study for determining the prevalence and risk factors of S. stercoralis infection. They found that strongyloidiasis was seen more often in male patients with eosinophilia and with HIV infection (9). Despite the fact that prevalence rates of infection are higher in the individuals with HIV, some researchers report that hyperinfection syndrome is rarely seen in advanced HIV disease because of increased Th2 response which may protect against severe forms of strongyloidiasis (16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…The estimated prevalence of strongyloidiasis in India has been found to be 6.6% and 11.2% in community and hospital based surveys respectively [1]. Several studies have shown an increase in incidence of infection with Strongyloides stercoralis in HIV infected population but only a handful of cases with severe manifestations have been noted in these individuals [6,7]. This is largely because, there is loss of Th1 activity in HIV infection but Th2 activity is well preserved which provides protection against development of severe manifestations [8].…”
Section: Discussionmentioning
confidence: 99%